EXPRESSION OF THE DESCRIPTIVE TERMS IN THE PROZE REPRESENTATION OF THE EPIC “FARKHAD AND SHIRIN” (Scientific journal of the Fergana State University, 2024)
This article describes artistic visual means and their theoretical foundations, the scope of their use in the epic of the great poet Alisher Navoi “Farhad and Shirin”, and also comments on the examples given for metaphor, one of the types of artistic visual means. The purpose of the study is to study the scope of use of artistic visual means in the epic “Farkhod and Shirin”. The research method is an analysis method that identifies visual means in the prose narrative of the epic and divides them into types: metaphor, metonymy, comparison. As a result of the study, artistic visual media were extracted and analyzed. The types of migrations are identified, their use, synonymy and homonymous phenomena are determined. Visual means were theoretically studied, and the samples in the work were scientifically studied.